Pertemuan Keluarga dalam Praktik di Layanan Primer - Retno Asti Werdhani; Dhanasari Vidiawati Trisna (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
From the Epidemiology Triangle, we can see that a person’s health status is influenced by 3 factors: host, agent, and the environment. The environment plays the biggest role as the cause of health prob-lems, one of which is the family environment.1Family can become a supporting factor or inhib-iting factor in the successful management of pa-tient’s cases. Therefore, a primary care physician/family physician needs to conduct family meetings to discuss and agree on solutions with the patient’s family by paying attention to inhibiting and sup-porting factors and find common solutions for the benefit of the patient.2,3